Ultrasonic Investigations of Inclusion Complexation of α-Cyclodextrin by DMSO in Pseudo-Binary Aqueous System - KACZMAREK-KLINOWSKA, Milena Maria; HORNOWSKI, Tomasz; SKUMIEL, Andrzej; JAŻDŻEWSKA, Monika (Archives of Acoustics, 2015)
The paper reports the study of the complexation processes in aqueous solution of α-CD and DMSO. Cyclodextrins (CDs) (sometimes called cycloamyloses) are cyclic oligosaccharides formed by glucose units interconnected by α-(1,4) linkages; α-CD is one of three the most common CDs. It consists of six glucopyranose units. The speed of ultrasonic waves has been measured by the resonance method on ResoscanTM System apparatus. Some collateral data, such as density and heat capacity of the system, have also been measured. On the basis of the experimental data the excess adiabatic compressibility was determined. The extremes of the excess adiabatic compressibility function for different mixture compositions allowed us to establish the composition of molecular complexes formed in the solution. The obtained results suggest the formation of the α-CD with DMSO inclusion complexes with chemical stoichiometric ratio value of 1:1.